Analisis Ergonomi Kursi Kereta Api: Systematic Literature Review - Rahmaniyah Dwi Astuti (Jurnal Rekayasa Sistem Industri, 2023)
The train is a popular mode of mass transit for a large number of passengers in Indonesia since it is reasonably priced. However, the existing passenger seats still do not pay attention to anthropometric measurements for Indonesian culture. The UIC standard, which is used as a standard for creating train seats, demonstrates this. Anthropometry is a science that involves measuring the human body and is used to identify variations between people, groups, and other entities. Ergonomic passenger seat design will have a good effect on both the company and the user. This study set out to ascertain the advantages of applying ergonomics to industrial tasks. A thorough literature review of 20 publications and papers published between 2012 and 2022 was done for this study. The results obtained are that there are many industrial activities that apply ergonomics to achieve comfort and the benefits of implementing ergonomics are new design recommendations and design development, knowing the relationship of vibration and energy to comfort, reducing discomfort, activities that affect comfort, the ability to estimate body size, knowing the risks diseases that arise, and knowing the level of importance of ergonomics.